A comparison of intrathecal dexmedetomidine, clonidine, and fentanyl as adjuvants to hyperbaric bupivacaine for lower limb surgery: A double blind controlled study - Vidhi Mahendru; Anurag Tewari; Sunil Katyal; Anju Grewal; M Rupinder Singh; Roohi Katyal (Wolters Kluwer Medknow Publications, 2013)
Background: Various adjuvants are being used with local anesthetics for prolongation of intraoperative and postoperative analgesia. Dexmedetomidine, the highly selective 2 adrenergic agonist is a new neuraxial adjuvant gaining popularity. Aim: The purpose of this study was to compare the onset, duration of sensory and motor block, hemodynamic effects, postoperative analgesia, and adverse effects of dexmedetomidine, clonidine, and fentanyl used intrathecally with hyperbaric 0.5% bupivacaine for spinal anesthesia. Settings and Design: The study was conducted in prospective, double blind manner. It included 120 American Society of Anesthesiology (ASA) class I and II patients undergoing lower limb surgery under spinal anesthesia after approval from hospital ethics committee with written and informed consent of patients. Materials and Methods: The patients were randomly allocated into four groups (30 patients each). Group BS received 12.5 mg hyperbaric bupivacaine with normal saline, group BF received 12.5 mg bupivacaine with 25 g fentanyl, group BC received 12.5 mg of bupivacaine supplemented 30 g clonidine, and group BD received 12.5 mg bupivacaine plus 5 g dexmedetomidine. The onset time to reach peak sensory and motor level, the regression time of sensory and motor block, hemodynamic changes, and side effects were recorded. Results: Patients in Group BD had significantly longer sensory and motor block times than patients in Groups BC, BF, and BS with Groups BC and BF having comparable duration of sensory and motor block. The mean time of two segment sensory block regression was 147 ± 21 min in Group BD, 117 ± 22 in Group BC, 119 ± 23 in Group BF, and 102 ± 17 in Group BS (P < 0.0001). The regression time of motor block to reach modified Bromage zero (0) was 275 ± 25, 199 ± 26, 196 ± 27, 161 ± 20 in Group BD, BC, BF, and BS, respectively (P < 0.0001). The onset times to reach T8 dermatome and modified Bromage 3 motor block were not significantly different between the groups. Dexmedetomidine group showed significantly less and delayed requirement of rescue analgesic. Conclusions: Intrathecal dexmedetomidine is associated with prolonged motor and sensory block, hemodynamic stability, and reduced demand of rescue analgesics in 24 h as compared to clonidine, fentanyl, or lone bupivacaine.